Double inferior vena cava, an uncommon but relevant anatomical anomaly in surgery for lower rectal cancer: a report of two cases - Mikio Kawamura; Shinji Yamashita; Hiroki Imaoka; Tadanobu Shimura; Takahito Kitajima; Yoshinaga Okugawa; Yoshiki Okita; Masaki Ohi; Yuji Toiyama (Surgical Case Reports, 2023)
Abstract Background Double inferior vena cava (DIVC) is rare and usually detected incidentally. DIVC may be associated with several anatomical variants of the retroperitoneal and pelvic veins. These variants can pose a clinical problem during colorectal surgery. We present two patients with lower rectal cancer who also had a DIVC. Case presentation Case 1 was a 72-year-old man with advanced lower rectal cancer (T3N0M0) who underwent robot-assisted low anterior resection after neoadjuvant therapy. A DIVC was detected on preoperative computed tomography (CT). During the operation, a presacral vein was injured while mobilizing the rectum and hemostasis could not be achieved. We converted to open surgery and packed the pelvic cavity for hemostasis. Retrospective analysis suggested the injured vein arose from an interiliac vein of the presacral pelvic venous plexus. Case 2 was a 50-year-old woman with lower rectal cancer (T3N0M0), immune thrombocytopenic purpura, and a DIVC. Although preoperative three-dimensional CT angiography showed no obvious pelvic vein abnormalities, a short course of preoperative radiotherapy was delivered to avoid lateral pelvic lymph node dissection. Chemotherapy was deferred owing to her thrombocytopenic disease. Laparoscopic abdominoperineal resection was performed meticulously to minimize bleeding and achieve rapid hemostasis. No intraoperative complications occurred. Conclusion DIVC is often accompanied by venous malformations that may pose a problem when mobilizing the mesorectum from the retroperitoneum. Preoperative assessment of pelvic vessel anatomy using three-dimensional CT is essential in patients with a DIVC who undergo rectal surgery.